Recognition of foreign divorce: a comparative vision between the Latin American and European systems: notes from the Peruvian jurisprudence in the recognition of no judicial divorces - Cabello Matamala, Carmen Julia (2015)
This article approaches a topic of increasing incidence in the judiciary system that is the recognition of foreign sentences because of the massive migratory movements currently produced by several factors causing a great economic, social, legal impact and in the relationships of the personnel involved in the family. In this topic is worth noting, the standarization of notary and administrative divorces, whose regulation in the civil laws is spreading in Latin America, although they do not receive similar recognition in the private international law.